Investigation on the Nitrogen Fixing Cyanobacteria (BGA) in Rice Fields of North-West Region of Bangladesh. I: Nonfilamentous - Hasan, MA (Journal of Environmental Science and Natural Resources, 2013)
The experiment was conducted to carry out the nitrogen fixing cyanobaterial (BGA) resources and their distribution pattern in rice fields of North-West region of Bangladesh during the period of 2011. Considering the vast importance of Blue-green algae (BGA) in agricultural land especially in rice fields, twelve months long systematic observation was undertaken. A total of 15 genera with 42 species of non-filamentous (unicellular and colonial) blue-green algal forms were identified and recorded from this region. Out of 42 species, 9 species belonging to the genus Aphanocapsa, 8 to Chroococcus, 5 to Gloeocapsa, 4 to Aphanothece, 3 to Gloeothece, 3 to Merismopedia and 2 to Coelosphaerium; while 1 species belonging to each genus of Chroococcidiopsis, Synechococcus, Synechocystis, Dactylococcopsis, Microcystis, Myxosarcina, Hydrococcus and Xenococcus. The distribution pattern of non-filamentous BGA in rice fields over the study area has also been observed in this study. With few exceptions, the non-filamentous BGA are more or less uniformly distributed all over the study areas. All of the BGA members have a tremendous ability to contribute on enhancing agricultural production by fixing atmospheric nitrogen and adding organic matter, vitamins, growth promoting substances etc to the soil and crops. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14812 J. Environ. Sci. & Natural Resources, 5(2): 185-192 2012